SPICE modeling of cycle-to-cycle variability in RRAM devices. (November 2021) - Salvador, E.; Gonzalez, M.B.; Campabadal, F.; Martin-Martinez, J.; Rodriguez, R.; Miranda, E.
Highlights: Uncorrelated cycle to cycle variability is included in the quasistatic memdiode model for RRAM devices. The best parameter distributions from experimental curves are extracted using fitdistrplus package from the R language. Model results reproduce the main features exhibited by the experimental curves. Statistical distributions from experimental and simulated parameters are compared. Abstract: In this work, we investigated how to include uncorrelated cycle-to-cycle (C2C) variability in the LTSpice quasi-static memdiode model for RRAM devices. Variability in the I-V curves is first addressed through an in-depth study of the experimental data using the fitdistrplus package for the R language. This provides a first approximation to the identification of the most suitable model parameter distributions. Next, the selected candidate distributions are incorporated into the model script and used for carrying out Monte Carlo simulations. Finally, the experimental and simulated observables (set and reset currents, transition voltages, etc.) are statistically compared and the model estimands recalculated if it is necessary. Here, we put special emphasis on describing the main difficulties behind this seemingly simple procedure.